The efficacy and safety of immune checkpoint inhibitors in metastatic castration-resistant prostate cancer: A systematic review and meta-analysis. Issue 31 (5th August 2022) - Wang, Xing-Hui; Wang, Zhi-Qiang; Mu, Zhen-Yu; Zhu, Li-Ping; Zhong, Chong-Fu; Guo, Shanchun
Abstract : Background: We aim to assess the efficacy and safety profiles of immune checkpoint inhibitors in patients with metastatic castration-resistant prostate cancer using a meta-analysis. Methods: We extracted and examined data from phase I, II and III clinical trials from PubMed, Embase, Web of Science, and Cochrane Library, which included patients with metastatic castration-resistant prostate cancer who were treated with immune checkpoint inhibitors. We performed a meta-analysis to investigate several indexes of efficacy and safety, including the objective response rate, 1-year overall survival (OS) rate, prostate-specific antigen response rate, and adverse event rate of immune checkpoint inhibitors. The material data were calculated and pooled using The R Project for Statistical Computing and STATA 12.0 software. Results: We identified 12 clinical trials in our study. We assessed the pooled frequencies of all-grade AEs and grade ≥ 3 AEs first and showed 0.82 (95% CI: 0.74–0.91, I 2 = 94%, P < .01) and 0.42 (95% CI: 0.33–0.54, I 2 = 96%, P < .01), respectively. The objective response rate was 0.10 (95% CI: 0.04–0.19, I 2 = 70%, P < .01), and the 1-year OS and prostate-specific antigen response rate were 0.55 (95% CI: 0.45–0.67, I 2 = 93%, P < .01) and 0.18 (95% CI: 0.16–0.20, I 2 = 43%, P = .03), respectively. Conclusion: The immune checkpoint inhibitors therapy was well tolerated and showed potential to improve tumor responses in patients with metastatic castration-resistant prostate cancer.